CLINICAL OUTCOMES OF LIMA-LAD AND RSVG-LAD ANASTOMOSES IN CORONARY ARTERY BYPASS GRAFTING SURGERY- SINGLE CENTER 3 YEARS EXPERIENCE - SAJJAD , MW; AYUB , W; ULLAH , S; FARSI , MS; MAHMOOD , A; JAN , A; KHAN , MI; ALI , N; AZIZ , Y; KHAN , MH; ULLAH , H; SHABIR , S; et al. (Biological and Clinical Sciences Research Journal, 2024)
Coronary artery bypass grafting (CABG) is a crucial intervention for managing ischemic heart disease, with successful revascularization of the left anterior descending (LAD) artery being essential for optimal outcomes. Various techniques and conduits are used in CABG, with the choice of graft significantly impacting patient prognosis. Objective: This study aimed to compare the clinical outcomes and morbidity associated with left internal mammary artery (LIMA) grafts versus reversed saphenous vein grafts (RSVG) to the LAD artery in patients undergoing isolated CABG. Methods: A retrospective observational study was conducted at a tertiary care hospital from January 2020 to December 2023. A total of 718 patients who underwent isolated CABG were included. The study received approval from the institutional review board, and all inclusion criteria were met. Patients were divided into two groups based on the type of graft used for the LAD artery: LIMA-LAD and RSVG-LAD. Statistical analysis was performed using Chi-square and T-tests, with data analyzed via SPSS version 25. A p-value of <0.05 was considered statistically significant. Results: The study included 718 patients with a mean age of 59.67 ± 9.270 years, predominantly male (74.7%), and with a majority classified as NYHA functional class III (46.0%). Hypertension was the most common comorbidity (67.1%), followed by dyslipidemia (58.0%) and diabetes mellitus (48.2%). The RSVG-LAD group had significantly older patients and a higher prevalence of hypertension, diabetes, tobacco smoking, and previous myocardial infarction. LIMA-LAD patients required more intraoperative blood product transfusions and had significantly longer cross-clamp times. However, the RSVG-LAD group exhibited worse morbidity outcomes, including significantly longer initial hours of mechanical ventilation and prolonged ventilation. Despite these differences, the two groups had no statistically significant difference in in-hospital mortality. Conclusion: This study confirms that LIMA-LAD anastomosis offers superior clinical outcomes and reduced morbidity compared to RSVG-LAD anastomosis. These findings highlight the advantages of using arterial grafts over vein grafts in coronary artery bypass surgery, particularly in reducing post-operative complications and improving overall patient prognosis.